2012
DOI: 10.1371/journal.pone.0050208
|View full text |Cite
|
Sign up to set email alerts
|

Placental Growth Factor for the Prediction of Adverse Outcomes in Patients with Suspected Preeclampsia or Intrauterine Growth Restriction

Abstract: BackgroundThe circulating concentration of PlGF is reported to be lower in patients experiencing preeclampsia and patients delivering a small for gestational age (SGA) neonate. To evaluate the predictive value of circulating PlGF for preeclampsia and adverse outcome in patients with suspected preeclampsia or intrauterine growth restriction (IUGR).Methodology/Principal FindingsA double blind prospective study. We enrolled 96 women for suspected preeclampsia or IUGR, and measured plasma levels of PlGF (Triage®) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 42 publications
7
58
0
1
Order By: Relevance
“…We recruited all those who were approached, eligible, and consented but did not document women who declined to take part. Of consented women, 24 did not have a valid baseline sample (17) or were lost to follow-up (7). The characteristics of the remaining 625 women are shown in Table 1, maternal and infant outcomes are in Table 2, details of adverse maternal and perinatal outcomes are in Tables I and II in the online-only Data Supplement, respectively, and unadjusted PlGF concentrations by final diagnosis are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recruited all those who were approached, eligible, and consented but did not document women who declined to take part. Of consented women, 24 did not have a valid baseline sample (17) or were lost to follow-up (7). The characteristics of the remaining 625 women are shown in Table 1, maternal and infant outcomes are in Table 2, details of adverse maternal and perinatal outcomes are in Tables I and II in the online-only Data Supplement, respectively, and unadjusted PlGF concentrations by final diagnosis are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…This prospective observational study was undertaken between January 2011 and February 2012 in 7 consultant-led maternity units in the (24) 19 (7) 11 (4) 88 (64) 27 (20) 13 (9) 9 (7) 151 (75) 25 (12) 12 (6) 13 (7) Highest 1st trimester systolic BP, (73) 10 (7) 22 (17) 101 (76) 19 (9) 30 (15) 151 (76) Previous medical history Previous preeclampsia Previous preeclampsia requiring delivery <34/40 55 (20) 30 (11) 17 (12) 6 (4.4)…”
Section: Methodsmentioning
confidence: 99%
“…This simple, quantitative, rapid test outperformed the standard battery of clinical diagnostic measures including blood pressure, proteinuria, uric acid, and other laboratory assays 57 . Importantly, sFlt1 and/or PlGF levels at presentation were strongly associated with the remaining duration of pregnancy 53,[57][58][59][60] . We also recently evaluated the role of sEng measurements and found that it has comparable performance to sFlt1/PlGF ratio 61 .…”
Section: Clinical Implications For Diagnosis and Treatment Of Preeclamentioning
confidence: 96%
“…Serum levels of PLGF are also reduced in the second and third trimesters of pregnancies that develop PE or deliver SGA neonates. 7,[13][14][15][16][17][18][19][20][21][22][23] While the pathophysiology of preeclampsia is not yet fully understood, there is growing evidence associating angiogenic proteins in screening, diagnosing and predicting the clinical course of the condition. 8,10,24,25 Placental growth factor (PLGF) is a proangiogenic marker that circulates at high concentrations in normal pregnancies.…”
Section: Introductionmentioning
confidence: 99%